2015
DOI: 10.2147/mder.s51189
|View full text |Cite
|
Sign up to set email alerts
|

Automated cyclers used in peritoneal dialysis: technical aspects for the clinician

Abstract: Peritoneal dialysis (PD) is a widely accepted and increasingly popular form of dialysis. The invention and technological advancement of the PD cycler further makes PD a convenient option. Prescription-specific parameters are entered into the cycler, which then automatically carries out the steps involved in continuous cycling PD. We review the basics, technical aspects, challenges, and advancements of the cycler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…According to Neri et al [9], the use of tidal PD optimized catheter ow function, resulting in the presence of < 1 alarm per day (corresponding to < 7 alarms per week). Accordingly, other authors suggest that out ow failure prompts alarms in APD patients treated with HomeChoicePro™ [10]. Moreover, the cut-off value for mean drain time of > 22 minutes for predicting catheter dysfunction found in our study is similar to the conclusion of other authors who suggested that a drainage time of less than 20 minutes is a marker of good catheter performance [3,18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to Neri et al [9], the use of tidal PD optimized catheter ow function, resulting in the presence of < 1 alarm per day (corresponding to < 7 alarms per week). Accordingly, other authors suggest that out ow failure prompts alarms in APD patients treated with HomeChoicePro™ [10]. Moreover, the cut-off value for mean drain time of > 22 minutes for predicting catheter dysfunction found in our study is similar to the conclusion of other authors who suggested that a drainage time of less than 20 minutes is a marker of good catheter performance [3,18].…”
Section: Discussionsupporting
confidence: 90%
“…Patients with a malfunctioning catheter may clinically present with slow drainage of PD uid, prolonged drain times, poor net UF [6,7] or constant alarms during cycler treatment [10], resulting in impairment of quality of life. Early diagnosis prevents the possibility of volume overload and complications associated with increased intraperitoneal volume that subsequently may lead to technique failure [11].…”
Section: Discussionmentioning
confidence: 99%
“…Last generation cyclers incorporate intra-peritoneal pressure (IPP) control, (pump-driven) inflow/outflow rate sensor, possibility to vary PDF composition, volume and dwell duration on a cycle by cycle basis during a session, giving room to better comfort for patients and caregivers while enhancing dialytic efficiency. 9 Technological innovation has also made remote monitoring possible, with the advantage of closer, real time follow up. It has been found to improve patient's adherence to prescribed therapy, to enhance timely recognition of complications and proactive intervention, to reduce patient's unscheduled access to the hospital and to promote dialysis adequacy.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Currently, the common treatments for uremia include kidney transplantation, hemodialysis(HD), hemoperfusion(HP) and peritoneal dialysis(PD) [3,4]. Despite many advances in the field of renal replacement therapy [5], patients still need long-term and frequent blood purification treatment in hospitals [6,7], which prevents them from returning to the society and restricts their personal freedom, which makes ESRD patients gradually marginalized by society and become a heavy burden to their families [8,9].…”
Section: Introductionmentioning
confidence: 99%